Sex differences in the association of BMI and weight perception with depression and suicidality among Korean adolescents - Eunha Jeong (PLoS ONE, 2025)
This study aimed to investigate sex-based differences in the effects of weight perception on depression and suicidality in Korean adolescents with and without obesity. A multiple logistic regression analysis stratified by sex was conducted using the 2023 Korea Youth Risk Behavior Survey data of 51,462 middle and high school students. BMI-based obese adolescents comprised a higher proportion of male participants (22.5%) than female participants (17.4%). The rate of underweight perception was higher among male participants (32.4%) than among female participants (23.3%); however, the rate of overweight perception was higher among female participants (37.3%) than among male participants (36.0%). The risk of depression or suicidality was higher among female participants (30.7% and 18.2%, respectively) than among male participants (21.3% and 10.7%, respectively). In female participants without obesity, the risk of depression and suicidality with overweight perception increased by 1.106 times (95% confidence interval [CI] 1.020–1.199) and 1.295 times (95% CI 1.176–1.427), respectively, compared to that with underweight perception as the reference group. However, this difference was not statistically significant among male participants without obesity. The findings of this study suggest that to improve the mental health of adolescents, proper weight recognition education along with obesity prevention should be implemented, and sex-specific interventions should be considered.